Diversification of energy resources as one of the ways to develop energy security of Ukraine - Zabarylo, O. V.; Korotkykh, Yu. A.; Zabarylo, P. O.; Забарило, Олексій Віталійович; Коротких, Юлія Анатоліївна; Забарило, Павло Олексійович (Харківський національний автомобільно-дорожній університет, 2025)
The article voices the need to strengthen the country's energy security, in particular through the course towards energy independence. The diversification of energy sources is defined as one of the tools that contributes to the development of the energy sector with specific examples of the implementation of such a policy in developed EU countries, and the main stages of its implementation in Ukraine are also voiced. The potential of Ukraine is characterized in terms of renewable energy sources and the possibilities of their development against the background of the gradual abandonment of imported fossil fuels. The prospects for further research to improve the management process of energy generation sources are voiced.
Диверсифікація енергоресурсів як один із напрямів розвитку енергетичної безпеки України
Keywords: alternative energy; energy efficiency; diversification; energy security; energy resources; альтернативна енергетика; енергоефективність; диверсифікація; енергетична безпека; енергетичні ресурси; 620.9; 10.30977/BUL.2219-5548.2025.108.0.193